Social Morbidity in Relation to Bowel Functional Outcomes and Quality of Life in Anorectal Malformations and Hirschsprung's Disease - Kyrklund, Kristiina; Neuvonen, Malla I.; Pakarinen, Mikko P.; Rintala, Risto J. (European Journal of Pediatric Surgery, 2018)
Background Anorectal malformations (ARMs) and Hirschsprung's disease (HD) are chronic bowel conditions associated with varying degrees of fecal incontinence. We aimed to discuss the contemporary status of social morbidity associated with ARMs and HD in the long term after contemporary treatments.Materials and Methods The bowel functional outcomes of our recent institutional series up to adulthood were reviewed and compared for ARMs and HD. The Rintala score was used to evaluate bowel function, which includes an assessment of the social effects of the condition. In this study, the social outcomes in our population of patients with ARMs and HD were specifically analyzed in relation to the surveyed functional outcomes, our previously collected data on quality of life (QoL) and the current literature.Results Mild ARMs were associated with a minimal risk of social morbidity consistent with good outcomes. In severe ARMs and HD, social problems were reported steadily among all age groups studied. Impairment of domains of fecal control were present among 53 to 89% of patients with social problems, including frequent symptoms (>1/week) in up to 39%. Involuntary gas leakage contributed to social morbidity in 15 to 27%. Comparison with QoL data suggested that social morbidity experienced during childhood may continue to affect emotional domains of QoL in later life, despite improvements in bowel function by adulthood.Conclusion Patients with severe ARMs and HD are at risk of social restrictions from impairment of bowel function despite contemporary surgical treatments. However, the QoL outcomes in adulthood may be more influenced by self-perceptions of illness formed from childhood than disease-specific factors. Strategies to reduce the psychological morbidity associated with these conditions that includes parental involvement from the outset may improve outcomes.
Keywords: anorectal malformations; Hirschsprung's disease; social morbidity; quality of life